Up-to-date criminal reference, 1994-1999 (Dhaka : Bangladesh Law Chronicles, 2000)
Reference work of Bangladesh Law Chronicles.
Keywords: Criminal procedure -- Bangladesh -- Digests; Criminal law -- Bangladesh -- Digests